Analysis of bovine parainfluenza-3 virus replication in bovine embryonic lung cells by indirect fluorescent antibody and hemadsorption assays - Toth, Thomas E. (J Virol Methods, 1990)
The temporal manifestation of bovine parainfluenza-3 virus (BPI3V) proteins in the cytoplasm and on the surface of bovine embryonic lung (BEL) cells was characterized by indirect fluorescent antibody (IFA) and hemadsorption (HAd) assays. Intracellular proteins appeared earliest at 0.5 h post inoculation (p.i.) and the infection spread to virtually all cells by 48 h p.i. Viral proteins on the surface of cells were seen first at 16 h p.i., and by 48 h p.i. the entire cell monolayer was IFA positive. Hundred-fold less virus in the inoculum delayed appearance of the intracellular as well as cell-surface viral proteins by 24 h and allowed the infection of only about 13 of the cells by 48 h p.i. Kinetics of the development in the proportion of HAd-positive cells correlated with those of the surface fluorescence-positive cells. Morphology of the manifestation of BPI3V proteins is characterized by microphotography.